Comparison of Autoimmune Thyroid Disease in Patients With Progressive and Stable Vitiligo. Issue 2 (March 2016) - Yazdanpanah, Mohammad Javad; Seyedi Noghabi, Seyed Ali; Taghavi, Morteza; Afzal Aghaee, Monavar; Zabolinejad, Naghmeh
Background and Objective: Activity of vitiligo has not been considered as a patient selection criteria in previous studies; we decided to compare the presence of elevated thyroid auto-antibodies in patients with progressive and stable vitiligo. Methods: Seventy-two patients with vitiligo were examined for thyroid problems and were divided into 2 groups of stable and progressive vitiligo according to their history and physical examination. Anti-thyroid peroxidase antibodies (anti-TPO antibodies), thyroxine (T4), and thyroid stimulating hormone (TSH) levels were assessed for all patients. Results: Elevated levels of anti-TPO antibodies were observed in 43.7% of the patients with stable vitiligo and in 37.5% of patients with progressive vitiligo, which was not statistically significant ( P = .315). Conclusion: This study not only confirmed thyroid dysfunction in patients with vitiligo but also showed that there was no difference in thyroid dysfunction and anti-TPO antibody levels in the subgroups of patients with stable or progressive vitiligo.